Psychometric properties of the Inventory Automatic Thoughts for Linked Studies to antisocial and criminal behavior in high school students secondary school of educational institutions of the district of Comas, 2017 - Pérez Vásquez, Erik Roger (2017)
The purpose of the present study is to know the psychometric properties for investigations related to the antisocial and criminal behavior of the Automatic Thoughts Inventory of Ruiz and Lujan (1991). In the first stage of the study, the instrument was applied to 270 students of both genders, aged 14 to 17 years and attending the secondary level in different educational institutions at Comas district, in Lima. The results showed in the first stage the restructuration of the inventory of 15 dimensions (original version) to 7 dimensions, by means of the exploratory factorial analysis, obtaining in this way the construct validity of the instrument. In the second stage, the obtained dimensions showed correlation levels between acceptable items (ritc>0.20) confirming the reliability of the inventory in its final version. Finally, the Automatic Thoughts Inventory in its modified version was composed by 42 items distributed in 7 dimensions that attempt to identify automatic thoughts for studies related to antisocial and criminal behavior in adolescents.